Exploring a Dance/Movement Program on Mental Health and Well-Being in Survivors of Intimate Partner Violence During a Pandemic - Özümerzifon, Yasemin; Ross, Allison; Brinza, Tessa; Gibney, Gina; Garber, Carol Ewing (Frontiers in Psychiatry, 2022)
Aims: The aim of this study was to explore the feasibility and benefits of a 12-session dance/movement program for intimate partner violence survivors’ mental health and PTSD symptoms during the COVID-19 Pandemic. The specific purposes were fourfold: 1) To determine the feasibility of delivering a virtual dance/movement workshop program; 2) to examine the effects of the program on symptoms of PTSD and psychological distress; 3) to determine whether heart rate variability improves; and 4) to describe the individual and shared experiences of a subgroup of participants of the program. Methods: Forty-five women ages 23-48 years were randomized to a 12-session virtual creative dance/movement program or a usual care control group, and completed questionnaires about PTSD and mental health symptoms, general health, physical activity, and underwent a brief measurement of heart rate variability. A subset of the intervention group participated in a semi-structured focus group. Results: The results of the study showed that the female survivors of intimate partner violence who participated in the virtual workshops felt better, and they experienced improved affect and reduced tension. They found new ways to express themselves, attune to their bodies, learn new self-care habits, and build community as they engaged in the workshops. Over the course of the study, the participants’ symptoms of PTSD and psychological distress lessened. There were no changes in heart rate variability. Conclusions: This complex study was successfully completed during a global pandemic and resulted in improvements in some mental health symptoms and overall well-being. Given the importance of this work with intimate partner violence survivors, further work exploring dance/movement workshops for participants virtually and in-person is needed.